The representation of variable tone sandhi patterns in Shanghai Wu. Issue 1 (11th August 2021) - Yan, Hanbo; Chien, Yu-Fu; Zhang, Jie
Disyllabic verb-noun (V-N) items in Shanghai Wu have variable surface tone patterns: They can undergo either a rightward extension tone sandhi, which extends the lexical tone of the first syllable over the entire word, or tonal reduction on the first syllable. The current study investigates how the phonological properties of these alternation processes as well as variation influence how Shanghai speakers represent and access such words. We conducted an auditory-auditory priming lexical decision experiment on Shanghai V-N items that can undergo either tonal extension or tonal reduction with native Shanghai speakers. Each disyllabic target was preceded by monosyllabic primes with the canonical tone, the tonal-extension tone, the surface tone, or a tone unrelated to the tone of the first syllable of the targets. Results showed both canonical and tonal-extension priming effects, but no surface priming effect. Moreover, although more familiar V-Ns were recognized with shorter reaction time, the priming effect did not interact with speakers' familiarity ratings or sandhi preference ratings of the targets. These data are consistent with the interpretation that both the canonical and tonal-extension forms are represented in Shanghai speakers' mental lexicon due to tone sandhi variation, but the representation does not seem to be modulated by the frequencies of the variants. Also, together with findings from auditory priming studies of other tone sandhi patterns, the current study suggests that certain phonological properties of an alternation, such as its locality and transparency, influence the representation of words undergoing the alternation; but whether the alternation is structure-preserving does not seem to impact the representation.